The Influence of Price Perceptions and Promotion on Purchase Decisions of Gacoan Noodles in Surabaya City (Study on Shopee Food Application) - Levy Mochammad Tsaqif; Ugy Soebiantoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to determine the influence of price perception and promotions on the purchasing decisions of Mie Gacoan (a brand of instant noodles) in Surabaya City (a study conducted on the Shopee Food application). This research method is quantitative and involves a sample size of 96 respondents, determined based on the sampling technique according to Ghozali's guidelines. The population of this study consists of Mie Gacoan consumers in Surabaya City who have made purchases through the Shopee Food application. The sample for this research was obtained using purposive sampling, which means selecting samples based on specific criteria. The sample consists of respondents who have purchased Mie Gacoan in Surabaya City through the Shopee Food application. The data used in this research are primary and secondary data. The analysis technique used in this study is Partial Least Squares (PLS) with validity testing, reliability testing, and hypothesis testing. The results of this research prove that: (1) Price perception has a positive and significant influence on purchasing decisions. (2) Promotions have a positive and significant influence on purchasing decisions.